A Brief History of Cell Culture: From Harrison to Organs-on-a-Chip - Lincoln Gozzi Moro; Lucas Pires Guarnier; Maurício Fogaça Azevedo; Julia Amanda Rodrigues Fracasso; Marco Aurélio Lucio; Mateus Vidigal de Castro; Marlon Lemos Dias; Francislaine Aparecida dos Reis Lívero; João Tadeu Ribeiro-Paes (Cells)
This comprehensive overview of the historical milestones in cell culture underscores key breakthroughs that have shaped the field over time. It begins with Wilhelm Roux’s seminal experiments in the 1880s, followed by the pioneering efforts of Ross Granville Harrison, who initiated groundbreaking experiments that fundamentally shaped the landscape of cell culture in the early 20th century. Carrel’s influential contributions, notably the immortalization of chicken heart cells, have marked a significant advancement in cell culture techniques. Subsequently, Johannes Holtfreter, Aron Moscona, and Joseph Leighton introduced methodological innovations in three-dimensional (3D) cell culture, initiated by Alexis Carrel, laying the groundwork for future consolidation and expansion of the use of 3D cell culture in different areas of biomedical sciences. The advent of induced pluripotent stem cells by Takahashi and Yamanaka in 2006 was revolutionary, enabling the reprogramming of differentiated cells into a pluripotent state. Since then, recent innovations have included spheroids, organoids, and organ-on-a-chip technologies, aiming to mimic the structure and function of tissues and organs in vitro, pushing the boundaries of biological modeling and disease understanding. In this review, we overview the history of cell culture shedding light on the main discoveries, pitfalls and hurdles that were overcome during the transition from 2D to 3D cell culture techniques. Finally, we discussed the future directions for cell culture research that may accelerate the development of more effective and personalized treatments.